SAT0195 Optimization of biologic therapies in rheumatoid and psoriasic arthritis: a single-centre experience. (12th June 2018) - Sgrulletti, M.; Salemi, S.; Di Rosa, R.; Petruccelli, R.; Laganà, B.; Sorgi, M. L.; Meneguzzi, G.; Quarta, S.; Catoni, M.; Picchianti Diamanti, A.; Caporuscio, S.; Salerno, G.; et al.
Abstract : Background: A timely diagnosis and a suitable therapy allow a better control of disease activity and limit joint damage in autoimmune arthritis. Biological therapies played a key role, modifying disease natural history. However, the use of these drugs implies several risks and increases health-care costs [1]. This has raised a question: could be possible, in patients in a state of sustained remission or low disease activity (LDA), choose an optimized regimen of treatment? Recommendations provided by EULAR in 2013 includes this possibility, especially if biologic therapy is in association with DMARDs [2]. While optimized regimen has been attempted in different clinical trials with good results, strong evidences are currently lacking [3]. Objectives: The aim of our study was to analyse the effectiveness of optimization of biologic therapies in a cohort of patients with Rheumatoid and Psoriasic Arthritis (RA and PA). Methods: We retrospectively included patients undergoing optimized therapy in a cohort of 328 outpatients (190 RA, 128 PA) treated with first-line biologic therapy from 2006 to 2017. Optimization was considered as predefined dose downtitration and/or expansion of dose interval in patients with a sustained remission or LDA (DAS 28 -ESR <2.6 or 2.6–3.2 respectively, for at least 24 months). Relapse was defined by an increase in DAS28-ESR >20% over baseline or by the onset of at least one tender and swollen joint. Our principal end-points were: (I) estimate the proportion of subjects able to optimize therapy (II) define the rate of relapse at 6–12 and 24 months follow-up (FU) in patients undergoing optimization (III) compare the effectiveness of optimized therapy in RA and PA patients and value the rate of optimization in relation to different biologic drugs. Survival analysis (Kaplan-Meier Curves) and Chi Square test were used and a p value <0.05 was considered as statistically significant. Results: During FU, 15/190 (8%) RA patients and 16/138 (12%) PA patients reached a persistent LDA or remission and started the optimized biologic therapy. In survival analysis, rates of relapse at 6 months were 10 % and 0% in RA ad PA respectively, increasing to 21% and 8% at 12 months and finally to 48 % and 34% at 24 months. No significant differences emerged between the two groups. The use of Etanercept was associated with higher possibility to optimize biologic treatment (p=0.007). Conclusions: Biologic therapy optimization is a workable option in RA ad PA patients who reached persistent remission or LDA. In our cohort Etanercept seems to be the most promising drug. Further studies are needed to better define the predictive factors of response in order to identify eligible patients. References: [1] Keystone EC. Safety of biologic Therapies – an update. J. of Rheumatol2005;32(Supplement 74):8–12. [2] Smolen JS, Landewé R, Breedveld FC, et al. EULAR recommendations for the management of rheumatoidarthritis with synthetic and biological disease-modifying antirheumatic drugs: 2013 update. Ann Rheum Dis2014;73:492–509. [3] Maneiro JR, Perez-Pampin E, Salgado E, et al. Observational study of optimization of biologic therapies in rheumatoid arthritis: a single-centre experience. Rheumatol Int2014;34(8):1059–63. Disclosure of Interest: None declared